RESEARCH OF THE PECULIARITIES OF SOCIOPSYCHOLOGICAL CHARACTERISTICS IN PEOPLE OF YOUNG AGE WITH DIFFERENT LEVEL OF TRUST IN INTERPERSONAL RELATIONSHIP - I. Efremkina (Вестник университета, 2019)
The actual problem of studying trust and socio-psychological characteristics in people of young (student) age has been reflected. First-year students of the Penza universities participated in the research process. Based on the results of diagnostics, two groups of subjects were identified: with high and low levels of trust in interpersonal relationship. Then, in these groups, such socio-psychological characteristics as types of attitude towards others and the level of empathic abilities were investigated. Statistical analysis of the obtained results allowed to reveal significant differences in the styles (types) of interpersonal relationships, the level of development of empathic abilities among students with high and low levels of trust.